The Effect of Fertilizer and Variety Combinations in Determining Thermal units in Red Chili Plants (Capsicum annuum L.) - Jamilah, Hariratun; Hariyono, Didik (Plantropica: Journal of Agricultural Science, 2026)
Red chili (Capsicum annuum L.) is a vegetable commodity with high economic value. The level of fruit maturity when harvested is a factor that influences the physical and chemical quality of red chilies. The method that can be used to determine the right harvest time is by accumulating thermal units. So efforts are needed to maintain optimal environmental conditions in providing thermal units, namely by using varieties and applying fertilizer. The research aims to determine the thermal unit in red chili plants due to the influence of the combination of fertilizer and variety. The research was carried out from January to May 2024 in Tegalgondo Village, Karangploso District, Malang Regency. The tools used are a hoe, analytical scales, camera, maximum-minimum thermometer, stakes, and writing tools. The materials used are red chili seeds of Imperial 10 and Horison 97 varieties, goat manure, NPK 16:16:16, Urea and silver black plastic mulch. This research used a Randomized Block Design (RBD) with 6 treatment combinations and 4 replications, consisting of P1 (Imperial 10 variety + NPK fertilizer and manure), P2 (Imperial 10 variety + NPK fertilizer), P3 (Imperial 10 variety + manure), P4 (Horizon 97 variety + NPK fertilizer and manure), P5 (Horizon 97 Variety + NPK fertilizer), P6 (Horizon 97 Variety + manure). The research results showed that the lowest thermal unit values ​​were found in the Imperial + manure and NPK treatments in the growth and flowering phases, as well as Imperial and manure in the germination and ripening phases. The Imperial 10 + manure treatment had lower yields than the Horison 97 + manure and NPK treatment.